A head full of stories - Swallow, Su; Archbold, Tim (London : Zero to Ten, 2010)
It's Jack's story time but his head is too full of stories So he tries to empty his head, ready for a new one. He tells his Grandma a story, and his brother, even his cat But it doesn't work out quite as he had hoped.
B
150
B
Keywords: story; Fairytale